Effect of service quality against visitor loyalty through visitor satisfaction - Hidayat, Firman; Asnawi, Nur (MEC-J (Management and Economics Journal), 2019)
The success of a government intention is to the satisfaction of the community about the service provided by the intense, the quality of service, satisfaction, and validity are important aspects that must be considered so that government institutions can be considered successful in serving the community. The purpose of this study was to determine the direct effect of service quality on visitor satisfaction and visitor loyalty and the influence of visitor satisfaction on visitor loyalty and the influence of service quality on visitor loyalty through visitor satisfaction. From this background this research was carried out with the title "The Effect of Service Quality on Visitor Loyalty Through Visitor Satisfaction. (Study at Banyuwangi Public Service Mall, East Java) ".This study uses a quantitative approach, the sample in this study was 181 respondents. Data collection with questionnaires, interviews, and documentation. The data analysis technique used in this study is Partial Least Square (PLS).From the results of the study showed that there is a direct effect of service quality on visitor satisfaction and visitor loyalty, there is a direct influence of visitor satisfaction on visitor loyalty and there is an indirect effect of service quality on visitor loyalty through visitor satisfaction at the Banyuwangi public service mall.Keywords: Service Quality, Visitor Satisfaction, Visitor Loyalty